The Design Of Garment Enterprise Data Warehouse Using The TOGAF Framework - Ni Putu Sri Merta Suryani; Putu Bagus Indra Sukadiana Putra; Komang Oka Saputra (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2018)
Garment company is a company that is recyclingfabric into apparel. Processing through several phases i.e. Setupprocess materials, production planning to produce a product. Inthe garment companyhas units that administered by the manager.The unit i.e. warehouses, production, marketing, human resourcesand finance. As time goes by, followed by information technologywhich is increasingly growing, the company needs a system ofinformation that is in tune with the business processes of thecompany. For it takes a data warehouse technology, so need tobuilt an integrated information system between units. EnterpriseArchitecture is the method used in building an enterprisearchitecture. One of the frameworks used in building aninformation system is TOGAF. TOGAF is used as a step inestablishing a system of information in the future can support thebusiness activities of the company.